ANALISIS PEMANFAATAN FASILITAS PELAYANAN KESEHATAN KEBIDANAN PADA IBU BERSALIN - Megawati Sinambela; Siti Marlina (JURNAL KEBIDANAN KESTRA (JKK), 2019)
Health Service is a tool and or place that used to conduct health care efforts whether promotion, prevention, curation, or rehabilitation which conducted by central government, local government, and or community (PPRI No. 47 thn 2016). Observational research Methods is crossectional research design approach. The research was conducted in the Working Area Community Health Center of Kolang Tapanuli Tengah Regency. The population in this study were all maternity mothers between June to December 2017 in the work area of Health Center of Kolang Central Tapanuli Regency as many as 256 people, this research use Slovin formula, so the amount of research sample is 156 respondase.The result of Bivariate study showed that there was a significant relationship between: a) maternal age with utilization of midwifery care facility (p-= 0,001), b) there was a significant correlation between maternal education with utilization of midwifery care facility (p-= 0,001), c) there is a significant correlation between maternal job with utilization of midwifery care facility (p-= 0,002), d) there is a significant correlation between mother attitude with utilization of midwifery care facility (p-v= 0,002), e) exist (p- = 0.000,), there is a significant correlation between travel time and the utilization of health care facility of midwifery (p-= 0,000), f) there is a significant relationship between support families with utilization of midwifery care facilities (p- = 0,000), g) there is a significant relationship between means infrastructure with utilization of midwifery care facility (p-= 0,002), officer attitude factor is the most influencing factor in the utilization of midwifery health services. The supportive attitude of the officers will have a likelihood of 121 times in improving the utilization of maternal services in maternal mothers rather than the supportive attitude of the less supportive officers of maternity mothers.It is hoped that health workers community Health Center of Kolang Tapanuli Tengah can provide more information about the utilization of midwifery health service facilities to improve patient's health status and patient independence in order to utilize midwifery health care facilities Health Center of Kolang Tapanuli Tengah Regency